Corporate Governance Country Assessment : Chile - World Bank (Washington, DC, 2013)
Chile's equity market is fairly large and successful. The market capitalization of the 249 listed firms represented 89 percent of GDP at year-end, 2001. Corporate ownership is concentrated and pyramid structures are common. Business groups/conglomerates are the predominant corporate form. Institutional investors, especially pension funds, are active equity investors. The Securities Market Law and the Corporation Law form the legal framework governing the capital markets. The securities market is regulated by the Superintendence of Securities and Insurance (SVS). Overall, Chile scores well on the assessment on compliance with the OECD Principles, scoring "Observed" or "Largely Observed" for 14 of 23 Principles; no Principle is deemed "Not Observed." The policy recommendations may be grouped under three broad categories: legislative reform, institutional strengthening and voluntary/private initiatives. The report recommends further amending Corporation Law and Securities Market Law to increase transparency for investors; having more transparency in and accountability of the SVS; increasing resources for the SVS to strengthen its ability to conduct market surveillance; and preparing a road map to improve the general enforcement of investor property rights. Finally, the report proposes creating an Institute of Directors to provide training for supervisory board members, disseminate best practice, and promote dialogue between the public and private sectors.